Folk phytotherapy of the Amalfi Coast (Campania, Southern Italy). (Journal of ethnopharmacology, 2011)
Ethnopharmacological relevance: In the Amalﬁ Coast, Campania (Southern Italy) a total number of 102 plant species are used for medicinal purposes, with a total of 276 different uses, among which, 183 are new for the area and 34 are new for Italy. Materials and methods: Data were obtained through semi-structured interviews with 214 inhabitants of the study area. Results: Folk phytotherapy is intended mainly as a mode of primary health care in order to heal minor illnesses, and especially disease related to the respiratory, urogenital, skeletal and gastrointestinal systems and skin problems. Among the new uses, interesting are those of Lobularia maritima (L.) Desv. subsp. maritima against abdominal pains and in case of cold and coughs; of Calystegia sylvatica (Kit. in Schrad) Griseb as resolvent for pimples and of Santolina neapolitana Jourdan & Fourr., against cough. The knowledge of medicinal plants is mainly retained by middle aged housewives, even though, it is declining. Many remedies are shared in other Italian regions or Mediterranean countries, while some uses seem to be speciﬁc to the area. Conclusions: In the study area, the ethnobotanical medicinal knowledge seems to have many elements in common with other areas, but also many unique features. This rich tradition competes with modern ways of life: plants still play an important role in the health care practices, even if the related knowledge is disappearing.